KONSTRUKSI PERLINDUNGAN HUKUM DEBITUR DALAM PENYELESAIAN KREDIT BERMASALAH DENGAN PELAKSANAAN LELANG JAMINAN HAK TANGGUNGAN - Lusia Sulastri (Jurnal Pembaharuan Hukum, 2015)
The resolutions of non-performing loans with tendering guarantee Encumbrance often bring up the resistance of the debtor in the form of Civil Lawsuit filed to the District Court whichis due to the complexity of the auction and several weaknesses inherent in the Mortgage Law. Issues that will be examined is the debtor regarding the cause of resistance and constructinglegal protection for the debtor, which will then be analyzed by juridical reasons debtor resistance and constructing legal protection for debtors. With the use of methods of doctrinal research is normative juridical will be reviewed by the study of civil cases in the District Court Majalengka and Cirebon.Research into the problem of resistance debtor caused the weaknesses that exist in the Law on Mortgage in particular Article 6 and Article 20 were used as opportunities in filing opposition by the debtor. Clauses are not clear and are not firmly set on the definition of injury Promise of a debtor, limit the authority becomes the object of Encumbrance, and the main thingis the complexity of the auction mainly related to the determination of the value of the object of encumbrance limit unilaterally by the creditor is considered unnatura.Resistance debtor raises the conception of the construction of legal protection to the debtor will be maintained, as well as the Law on Consumer Protection which regulates legal protectionfor debtors and also provides protection against collateral in the debtor from the arbitrariness of the determination of the limit value by “ Tendering Crime “ in the tendering process the security object security rights. Weakness contained in UUHT and determination of limit values of objects in the tenderingprocess encumbrance become the subject matter of this study. For it is very important that creditors be cautious in making loans to its customers, in the handling of non-performing loans,especially the tendering security rights regarding the value of the object of the tender limit creditors should remain guided by the principles of good faith and respect for the property of a person.